Heat transfer aspects of condensation during vapour phase soldering on aligned PCB-based surfaces. Issue 4 (8th April 2020) - Straubinger, Daniel; Bozsóki, István; Illes, Balazs; Krammer, Oliver; Bušek, David; Geczy, Attila
Abstract : Purpose: The paper aims to present an investigation on heat transfer in a vapour phase soldering (VPS) oven, focusing on the differences of horizontally and vertically aligned Printed Circuit Board (PCB) surfaces. The investigation can help develop a better understanding of the process and provide information for future modelling of the process. Design/methodology/approach: For the investigations, flame retardant grade 4 (FR4) PCB plates and sealed plate–based boxes were immersed into saturated vapour of an experimental oven. The temperature and resulting heat transfer coefficients were analysed according to the sample boxes and the surface orientations. In addition, the boxes' vapour consumption was investigated with pressure measurements. Findings: The horizontal top- and bottom-side heating shows very similar results. In addition, the sides of a box were heated in a manner similar to the top and the bottom sides, but there was a slight increase in the heat transfer coefficient because of the vertical wall alignment. The pressure measurements reveal the dynamic changes in vapour after immersion of the boxes. Practical implications: The findings may help to show differences on different surface orientations, pointing to more precise, explicit and multiphysics simulation results. Originality/value: The experiments present an aspect of heat transfer coefficient differences in VPS ovens, also highlighting the effect of initial pressure drop inside the workspace of an oven.